Incident Learning and Failure-Mode-and-Effects-Analysis Guided Safety Initiatives in Radiation Medicine - Kapur, Ajay; Zuvic, Petrina; Goode, Gina; Riehl, Catherine; Joseph, Sherin; Adair, Nilda; Interrante, Michael; Bloom, Beatrice; Lee, Lucille; Sharma, Rajiv; Sharma, Anurag; Antone, Jeffrey; et al. (Frontiers in Oncology, 2013)
By combining incident learning and process failure-mode-and-effects-analysis in a structure-process-outcome framework we have created a risk profile for our radiation medicine practice and implemented evidence-based risk mitigation initiatives focused on patient safety. Based on reactive reviews of incidents reported in our departmental incident-reporting system and proactive failure-mode-and-effects-analysis, high safety-risk procedures in our paperless radiation medicine process and latent risk factors were identified. Six initiatives aimed at the mitigation of associated severity, likelihood of occurrence and detectability risks were implemented. These were the standardization of care pathways and toxicity grading, pre-treatment-planning peer review, a policy to thwart delay-rushed processes, an electronic whiteboard to enhance coordination and the use of six-sigma metrics to monitor operational efficiencies. The effectiveness of these initiatives over a three year period was assessed using process and outcome specific metrics within the framework of the department structure. There has been a 47% increase in incident reporting, with no increase in adverse events. Care pathways have been used with greater than 97% clinical compliance rate. The implementation of peer review prior to treatment planning and use of the whiteboard have provided opportunities for proactive detection and correction of errors. There has been a twofold drop in the occurrence of high-risk procedural delays. Patient treatment start delays are routinely enforced on cases that would have historically been rushed. Z-scores for high risk procedures have steadily improved from 1.78 to 2.35. The initiatives resulted in sustained reductions of failure-mode risks as measured by a set of evidence-based metrics over a three year period. These augment or incorporate many of the published recommendations for patient safety in radiation medicine by translating them to clinical practice.